Relationship between jump height and rate of braking force development in professional soccer players - Merino-Munoz, P.; Perez-Contreras, J.; Aedo-Munoz, E.; Gustamante-Garrido, A. (Journal of Physical Education and Sport, 2020)
Explosive force is the ability to increase force or torque as rapidly as possible during a voluntary contraction from a low level or at rest and is primarily quantified as the rate of force development (RFD). A high RFD is considered a determinant of sports performance. Vertical jump has been shown to be dependent on RFD, and this test is widely used to evaluate the explosive strength capability of the lower limbs, as it has been associated with other skills that are determinants in sport such as strength, power, speed, agility and changes of direction.Objective: To know the relationship between jump height (JH) and JH normalized to height subject (JHn) calculated through flight time (FT) and the rate of force development (RFD) of the eccentric braking phase. Method: The sample was of a total of 21 male professional soccer players, from to a first division B team in Chile (age = 24.4 ± 4.0 years; body mass = 76.4 ± 7.1 kg.; height = 1.77 ± 0.08 meters; experience = 7.0 ± 4.5 years). Vertical jump (CMJ) was evaluated using two PASCO PS-2142 force platforms. Statistical tests of association (Pearson's r) and prediction (linear regression) were performed. Results: No significant relationships were found between JH and JHnwith the variables for the RFD of the eccentric braking. Conclusion: From the results found in this study, it is possible to conclude that the jump height calculated through the flight time and normalized to the height of the subject, does not present a significant association with the rate of development of eccentric braking force and normalized to body weight, which allows recognizing that the jump height is not a direct indicator of explosive force of the lower limb.